An Exploration of Syndemic Factors that Influence Engagement in HIV Care Among Black Men - Quinn, Katherine G. (Qual Health Res, 2018)
Syndemic theory seeks to understand the interactions and clustering of disease and social conditions and explain racial disparities in HIV. Traditionally applied to HIV risk, this study characterizes the syndemic challenges of engagement in care among Black men living with HIV and provides insight into potential HIV treatment interventions to retain vulnerable individuals in care. Interviews were conducted with 23 HIV-positive men who were either out-of-care or non-adherent to antiretroviral therapy. Interviews were audio-recorded, transcribed verbatim, and coded using MAXQDA qualitative software. Researchers analyzed data using thematic content analysis to identify syndemic factors associated with disengagement in care or suboptimal ART adherence among Black men. Analyses revealed the syndemic nature of 4 themes: intersectional stigma, depression, substance use, and poverty. Findings from this study offer numerous opportunities for intervention including social and structural-level interventions to address syndemic processes and the influence of stigma and poverty on engagement in care.